Sheep - Gatenby, R.M.; Humbert, J.M. (Technical Centre for Agricultural and Rural Cooperation, 2002)
With its detailed presentation of characteristics and requirements, this booklet outlines how to raise sheep in a variety of tropical zones and farming systems. Topics covered in a comprehensive and easy-to-follow style include: breeding, health, nutrition and processing and production of meat, wool, skins and milk.